2011
DOI: 10.1002/hep.24484
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin and liver fibrosis: Hitting three birds with one stone?

Abstract: PDGF-dependent hepatic stellate cell (HSC) recruitment is an essential step in liver fibrosis and the sinusoidal vascular changes that accompany this process. However, the mechanisms that regulate PDGF signaling remain incompletely defined. Here, we found that in two rat models of liver fibrosis, the axonal guidance molecule neuropilin-1 (NRP-1) was upregulated in activated HSCs, which exhibit the highly motile myofibroblast phenotype. Additionally, NRP-1 colocalized with PDGFreceptor beta (PDGFRbeta) in HSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…In addition to NRP’s potential as an anti‐cancer agent, recent findings indicate that NRP may also influence fibrosis via PDGF and TGF‐β1 signalling and therefore, with angiogenesis and VEGF also shown to have important roles in fibrosis (Yoshiji et al. 2003), the potential of targeting NRP1 to ‘hit three birds with one stone’ as an antifibrotic agent has also been suggested (Troeger & Schwabe 2011).…”
Section: Neuropilins As Therapeutic Targets and Translational Advancesmentioning
confidence: 99%
“…In addition to NRP’s potential as an anti‐cancer agent, recent findings indicate that NRP may also influence fibrosis via PDGF and TGF‐β1 signalling and therefore, with angiogenesis and VEGF also shown to have important roles in fibrosis (Yoshiji et al. 2003), the potential of targeting NRP1 to ‘hit three birds with one stone’ as an antifibrotic agent has also been suggested (Troeger & Schwabe 2011).…”
Section: Neuropilins As Therapeutic Targets and Translational Advancesmentioning
confidence: 99%
“…On the other hand, MMPs play an important role because their activity is largely responsible for matrix breakdown. 23 The results of previous study showed that circulating concentrations of the MMP-2 as well as TIMP-1 change in the course of liver fibrosis. MMP-2/TIMP-1 ratio has shown correlation to degree of fibrosis.…”
Section: Mmp-2 and Timp-1 Expressionmentioning
confidence: 99%
“…Οι νευροπιλίνες (neuropilins, NRPs) ταυτοποιήθηκαν αρχικά ως υποδοχείς για τις σεμαφορίνες (semaphorins) κλάσης 3, που είναι πολυπεπτίδια με σημαντικό ρόλο στο νευρικό σύστημα. Ακολούθως, βρέθηκε συμβάλλουν σε πολλά μονοπάτια σηματοδότησης, όπως αυτά των PDGF, TGF-β και VEGF [513][514][515] Ορισμένες μελέτες σε μοντέλα ηπατικής ίνωσης έδειξαν πως η NRP-1 παίζει ρόλο στην αγγειογένεση 514 . Σε ορισμένα πειραματικά μοντέλα ηπατικής ίνωσης, ένα εξουδετερωτικό αντίσωμα έναντι της NRP-1 μείωσε την παραγωγή VEGF σε καλλιέργειες ενδοθηλιακών κυττάρων 515 .…”
Section: νευροπιλίνες και αγγειογένεσηunclassified
“…Ακολούθως, βρέθηκε συμβάλλουν σε πολλά μονοπάτια σηματοδότησης, όπως αυτά των PDGF, TGF-β και VEGF [513][514][515] Ορισμένες μελέτες σε μοντέλα ηπατικής ίνωσης έδειξαν πως η NRP-1 παίζει ρόλο στην αγγειογένεση 514 . Σε ορισμένα πειραματικά μοντέλα ηπατικής ίνωσης, ένα εξουδετερωτικό αντίσωμα έναντι της NRP-1 μείωσε την παραγωγή VEGF σε καλλιέργειες ενδοθηλιακών κυττάρων 515 . Πιθανώς, τέτοιοι παράγοντες να αποτελέσουν στο μέλλον αντιινωτικές θεραπείες με στόχο τους αυξητικούς παράγοντες PDGF, TGF-β και VEGF στα χρόνια ηπατικά νοσήματα.…”
Section: νευροπιλίνες και αγγειογένεσηunclassified